2021
DOI: 10.1111/jcpt.13494
|View full text |Cite
|
Sign up to set email alerts
|

Vedolizumab‐associated pulmonary manifestations in children with ulcerative colitis

Abstract: Vedolizumab (VDZ) is a humanized monoclonal antibody and an antiintegrin molecule which interferes with lymphocytes trafficking in the inflamed gastrointestinal tract, therefore reducing immune cell infiltration and local inflammation. 1 In particular, VDZ is characterized by a gut selectivity thanks to its interaction with a4b7-integrin, which is expressed specifically by a subset of gastrointestinalhoming T lymphocytes. Such a blockade prevents the binding of a4b7-integrin-positive leukocytes to the mucosal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…These cells consequently remain in the pulmonary parenchyma, leading finally to tissue damage [169]. Recently, a case of a child experiencing VED-associated pulmonary disease was published, probably based on an integrin shift leading to proliferation of CD29 + lymphocytes (β1-integrin), which amplifies lymphocyte homing to the lung [170]. Mitchel et al reported the case of a child with non-infectious bilateral pneumonia after the initiation of immunosuppressive therapy with UST [171].…”
Section: Medication-associated Lung Injurymentioning
confidence: 99%
“…These cells consequently remain in the pulmonary parenchyma, leading finally to tissue damage [169]. Recently, a case of a child experiencing VED-associated pulmonary disease was published, probably based on an integrin shift leading to proliferation of CD29 + lymphocytes (β1-integrin), which amplifies lymphocyte homing to the lung [170]. Mitchel et al reported the case of a child with non-infectious bilateral pneumonia after the initiation of immunosuppressive therapy with UST [171].…”
Section: Medication-associated Lung Injurymentioning
confidence: 99%
“…More serious adverse events have been reported in single case studies. In two patients with UC, Pott’s puffy tumor ( 26 ) or persistent and productive cough ( 27 ) was described in response to treatment with vedolizumab.…”
Section: Introductionmentioning
confidence: 99%